Observing the ultrafast buildup of a Fano resonance in the time domain - Kaldun, Andreas; Blättermann, Alexander; Stooß, Veit; Donsa, S.; Wei, H.; Pazourek, R.; Nagele, S.; Ott, Christian; Lin, C. D.; Burgdörfer, J.; Pfeifer, Thomas (Science, 2016)
Watching as helium goes topsy-turvy - Theorists have long pondered the underpinnings of the Fano resonance, a spectral feature that resembles adjacent rightside-up and upside-down peaks. An especially well-studied instance of this feature appears in the electronic spectrum of helium as a transient state undergoes delayed ionization. Two studies have now traced the dynamics of this state in real time. Gruson et al. used photoelectron spectroscopy to extract the amplitude and phase of the electron wave packet after inducing its interference with reference wave packets tuned into resonance at variable delays. Kaldun et al. used extreme ultraviolet absorption spectroscopy to probe the transient state while variably forcing ionization with a strong near-infrared field. - Science, this issue pp. 734 and 738 - Although the time-dependent buildup of asymmetric Fano line shapes in absorption spectra has been of great theoretical interest in the past decade, experimental verification of the predictions has been elusive. Here, we report the experimental observation of the emergence of a Fano resonance in the prototype system of helium by interrupting the autoionization process of a correlated two-electron excited state with a strong laser field. The tunable temporal gate between excitation and termination of the resonance allows us to follow the formation of a Fano line shape in time. The agreement with ab initio calculations validates our experimental time-gating technique for addressing an even broader range of topics, such as the emergence of electron correlation, the onset of electron-internuclear coupling, and quasi-particle formation. - Ultrafast spectroscopy traces the dynamics of a transient excited state in helium underlying appearance of a Fano resonance. - Ultrafast spectroscopy traces the dynamics of a transient excited state in helium underlying appearance of a Fano resonance.
Gesehen am 07.05.2020